Physicians' views on cardiovascular disease risk prevention services by pharmacists and potential for collaboration - Hadi A. Almansour; Nouf M. Aloudah; Tariq M. Alhawassi; Betty Chaar; Ines Krass; Bandana Saini (Elsevier, 2021)
Background: Cardiovascular diseases (CVD) are the leading cause of mortality worldwide. Early identification and management of modifiable CVD risk factors are highly effective in preventing disease onset and/or improving outcomes in CVD. As highly accessible primary health professionals, pharmacists can assume a role in screening and risk factor management in collaboration with physicians; however, such prevention services are not established practice in Saudi pharmacies. Therefore, the aim was to explore physicians' perceptions about the utility of a role in CVD risk screening and management for Saudi pharmacists. Methods: Qualitative semi-structured interviews were conducted, audio-recorded and transcribed verbatim in Arabic or English. All transcripts were thematically analyzed in an inductive approach after translation into English if required. Results: A total of 26 physicians recruited from public hospitals and primary healthcare centers were interviewed. Most were unaware of pharmacists' potential to undertake a role in CVD risk prevention. Although there was broad support for the concept, they recommended physician-pharmacist collaborative models, extensive provider pharmacist training, and strict oversight by the Saudi Ministry of Health (MoH)/other official authorities to ensure service quality and sustainability, should implementation occur. Healthcare system reform was considered key to expanding private sector (i.e., community pharmacy) involvement in healthcare, as was incentivizing providers and 'marketing' for patient acceptance. Conclusion: Physicians were positive about setting up a collaborative community pharmacist-physician CVD risk screening and management service model with the help of an authorized body within the Saudi Arabian healthcare system.